Project Free-B: how investigating the socio-economic metabolism of rentier capitalism holds the key to sustainable socio-ecological wellbeing - Priels, Koenraad (University of Darussalam Gontor Press, 2024)
The purpose of this paper, is to demonstrate how capitalism as a system, is not required for the real economy but in fact, constitutes a parasitic superstructure that is causing socio-ecological necrosis. Consequently, credible systemic solutions to our global social and ecological crises should integrate sound awareness of pathological structures that are detrimental to a healthy socio-economic metabolism. As critical realism results in ethical imperatives from these findings, prosocial orthosociology presents systemic solutions. Project Free-B offers the possibility for a global interest-free financial system, beyond the need for the BIS-central banking system. The current global interest-banking system under BIS-regulation should be abolished as an institutionalised criminal system. On scrutiny, it proves to be socio-ecologically destructive by design and hence, constitutes a systemic violation of human rights.